The interplay of Criterion A of the Alternative Model for Personality Disorders, mentalization and resilience during the COVID-19 pandemic - Maerz, Jeff; Buchheim, Anna; Rabl, Luna; Riedl, David; Viviani, Roberto; Labek, Karin (Frontiers in Psychology, 2022)
Background and aims: The COVID-19 pandemic has been accompanied by deteriorating mental health issues. Nevertheless, many people remain resilient and manage to adapt or recover relatively soon, providing an opportunity to investigate risk and protective factors, as well as the role of individual resilience. As in recent theoretic approaches (Fonagy et al., 2017a; Kalisch et al., 2015), we were interested in verifying empirically the interplay between resilience and risk factors identified in dimensional diagnostic approaches to personality. Methods: We assessed the relationship between personality functioning (measured by Criterion A of the Alternative Model for Personality Disorders; AMPD) and mentalizing abilities as predictors, and depression and life satisfaction as mental health outcomes. Specifically, we were interested in testing the hypothesis that this relationship is mediated by resilience. Data from N = 316 individuals from the general population were collected. Results: Linear regression models revealed highly significant associations between Criterion A/mentalization and both outcome measures. Structural equation models showed a significant partial mediation by resilience of these relationships. Conclusion: Our results support the hypothesis that mentalizing serves as a protective function by promoting resilience to the impact of stress and threats. This finding emphasizes the importance of personality functioning as an indicator of severity of self-other impairments in healthy individuals in positive and negative mental health issues. Furthermore, our results showed that personality functioning is a decisive factor involved in the development of resilience.